Antibiotic resistance pattern of bacteria isolated from patients with upper respiratory tract infections; a four-year study in Tripoli city - Ahmed Atia (Emergency Department of Hospital San Pedro (Logroño, Spain), 2020)
Introduction: Respiratory tract infections have been known to be a significant health concern for mortality and morbidity since many years. This study was aimed at determining the prevalence of bacterial pathogen causing upper respiratory tract (URTIs) and the susceptibility patterns to frequently used antibiotics among patients attending Abusetta hospital in Tripoli district. Methods: A total of 1,110 throat swabs were collected between Jan, 2011 to December, 2014 and inoculated onto Blood agar, MacCkonkey agar and Chocolate agar then incubated at 37 oC for 24 hours. Bacterial pathogens were determined by bacteriological culture methods and antibiotic susceptibility of the isolates was identified following Clinical Laboratory Standard Institute guidelines (CLSI). Results: Of the 1,110 respiratory samples tested, 71.1% (n = 789) of specimens were positive cultures with the dominant bacterial pathogens being Streptococcus pneumoniae 43.3% (n = 342), followed by Pseudomona aeruginosa 22.8% (n = 180), Staphylococcus aureus 13.8% (n = 109), Escherichia coli 6.9% (n = 55), Enterobacter spp 6.2% (n = 49), Citrobacter 4.5% (n = 36), and Klebsiella 2.2% (n = 18). Most isolates exhibited resistance against the commonly used antibiotics and to at least one antibiotic. Conclusion: The level of antibiotic resistance in this study is alarming and brings to light the timely and suitable diagnosis of the common bacteria causes of URTIs and proper antibiotic administration based on susceptibility test.